Broadcasting one world: How watching online videos can elicit elevation and reduce stereotypes. (September 2017) - Krämer, Nicole; Eimler, Sabrina C; Neubaum, German; Winter, Stephan; Rösner, Leonie; Oliver, Mary Beth
Research on non-hedonic entertainment suggests the experience of elevation as an important construct leading to beneficial outcomes such as prosocial motivation. This study builds on first findings in this realm by distinguishing between different meaningful media contents. In a 3 × 4 between-subjects online experiment, we varied type of video (beauty of the earth, unity of humankind, portrayals of human kindness, and funny control videos) and context of proliferation (presentation on an unknown video platform or on YouTube with low vs high number of views). Meaningful videos indeed led to greater elevation, more universal orientation, and prosocial motivation—with videos showing human kindness standing out against other forms of meaningful videos. Human kindness videos additionally fostered more positive attitudes toward stereotyped groups—mediated by the feeling of elevation and the subsequent feeling of universal orientation.